(untitled) (Global Journal of Human-Social Science, 2025)
This study aims to determine the composition of the traditional government apparatus in the past in the Mamasa region and takes samples in the Sesena Padang traditional area one of the traditional areas that still exists to maintain presence until now and is also a partner of modern government in Mamasa Regency West Sulawesi Province The location of the study is Sesenapadang District Mamasa Regency The research variables consist of a the composition of traditional apparatus b the hadat government system and c the social environment of the hadat government The data in this study are the results of direct observation and documentation in the field The data were analyzed descriptively qualitatively and then used as a basis for drawing conclusions The results of the study show that 1 The composition of the customary apparatus consists of Tokeada Bali Ada Tomakbisara ada Pangngulu Basssi So bok Toma kada padang Sulewa na ada To Burake Tomakaka Toma kada Barata Toma gandang Tomebalun Ma dika Pande Bulawan Pande Bassi Tomanarang and Tomebalun 2 The customary government system is held by Tokeada assisted by Bali Ada and other customary apparatus according to their respective job functions 3 The social environment of society is regulated by customary law and is fully implemented by customary leaders according to their respective duties and functions